Exercise activates the hypothalamic S1PR1–STAT3 axis through the central action of interleukin 6 in mice. Issue 12 (31st July 2018) - Silva, Vagner R. R.; Micheletti, Thayana O.; Katashima, Carlos K.; Lenhare, Luciene; Morari, Joseane; Moura‐Assis, Alexandre; de Lima‐Júnior, José C.; Camargo, Juliana A.; Passos, Gabriela R.; Gaspar, Rodrigo S.; Velloso, Licio A.; Saad, Mario J.; et al.
Abstract : Hypothalamic sphingosine‐1‐phosphate receptor 1 (S1PR1), the G protein–coupled receptor 1 of sphingosine‐1‐phosphate, has been described as a modulator in the control of energy homeostasis in rodents. However, this mechanism is still unclear. Here, we evaluate the role of interleukin 6 (IL‐6) associated with acute physical exercise in the control of the hypothalamic S1PR1–signal transducer and activator of transcription 3 (STAT3) axis. Acute exercise session and an intracerebroventricular IL‐6 injection increased S1PR1 protein content and STAT3 phosphorylation in the hypothalamus of lean and obese mice accompanied by a reduction in food consumption. Transcriptome analysis indicated a strong positive correlation between Il‐6 and S1pr1 messenger RNA in several tissues of genetically diverse BXD mice strains and humans, including in the hypothalamus. Interestingly, exercise failed to stimulate the S1PR1–STAT3 axis in IL‐6 knockout mice and the disruption of hypothalamic‐specific IL‐6 action blocked the anorexigenic effects of exercise. Taken together, our results indicate that physical exercise modulates the S1PR1 protein content in the hypothalamus, through the central action of IL‐6. Abstract : Exercise, hypothalamic sphingosine‐1‐phosphate receptor 1, interleukin 6, and hypothalamus.